2022
DOI: 10.1177/10887679221101605
|View full text |Cite
|
Sign up to set email alerts
|

A New Wave of Mass Shootings? Exploring the Potential Impact of COVID-19

Abstract: Although the COVID-19 pandemic has brought much of U.S. society to a grinding halt, its impact on the occurrence of mass shootings is largely unknown. Using data from the Gun Violence Archive and an interrupted time-series design, we analyzed weekly counts of mass shootings in the U.S. from 2019 through 2021. Results show that total, private, and public mass shootings increased following the declaration of COVID-19 as a national emergency in March of 2020. We consider these findings in the context of their bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Despite the existence of a substantial body of knowledge relating to tourism risks, including those stemming from terrorism and political instability, there is a notable dearth of research concerning health risks in the tourism context (Donthu & Gustafsson, 2020;Jonas et al, 2011;. Previous studies in this domain have primarily been conducted under normal circumstances (Schildkraut & Turanovic, 2022), failing to capture the gravity of a pandemic like COVID-19 and its profound effects on the psychological well-being (Yavorsky et al, 2022) as well as behavioral intentions of travelers (Li et al, 2022). The recognition of risk formation related to perceived COVID-19, coupled with the dissemination of risk knowledge and travelers' willingness to adapt to outbreak scenarios, carries profound implications for industry stakeholders seeking to navigate this evolving landscape (Yan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of a substantial body of knowledge relating to tourism risks, including those stemming from terrorism and political instability, there is a notable dearth of research concerning health risks in the tourism context (Donthu & Gustafsson, 2020;Jonas et al, 2011;. Previous studies in this domain have primarily been conducted under normal circumstances (Schildkraut & Turanovic, 2022), failing to capture the gravity of a pandemic like COVID-19 and its profound effects on the psychological well-being (Yavorsky et al, 2022) as well as behavioral intentions of travelers (Li et al, 2022). The recognition of risk formation related to perceived COVID-19, coupled with the dissemination of risk knowledge and travelers' willingness to adapt to outbreak scenarios, carries profound implications for industry stakeholders seeking to navigate this evolving landscape (Yan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These stricter definitions will also discount the impact of gun violence on women and children who are vulnerable due to male-perpetrated domestic violence; indeed, 53% of mass shootings involve an intimate partner or a family member (Everytown for Gun Safety, 2019). Schildkraut and Turanovic (2022) point out that increased gun sales in 2020 may be associated with the increase in mass shootings during this time; indeed, there was a 40% increase in background checks for gun sales in the U.S. in 2020 with only a slight drop in 2021 (FBI, 2022).…”
mentioning
confidence: 99%
“…Mass shootings are a part of life in the U.S., where Americans own nearly 400 million firearms or 45.8% of the firearms in civilian possession across the world (Small Arms Survey, 2018). Schildkraut and Turanovic (2022) use the gun violence archive (GVA) to estimate the impact of COVID-19 on mass shootings, defined as when four or more people (not including the murderer) are killed in a single incident. The authors found that both public (e.g., at schools and workplaces) and private (e.g., at homes) mass shootings increased by approximately 50% after COVID-19 was declared a national emergency in March 2020.…”
mentioning
confidence: 99%
“…Studies and datasets use variations of this mass shooting definition to examine all mass shootings (e.g., Duwe, 2020;Gun Violence Archive, 2021;Mass Shooting Tracker, 2021) and to compare the different types of mass shootings (e.g., Silva, 2022a;USA Today, 2018). Most scholars agree that there are important differences between public and private/residential mass shootings (Duwe, 2004(Duwe, , 2020Schildkraut & Turanovic, 2022), and that private/residential mass shootings constitute unique forms of violence with critically different response and prevention strategies. For example, the perpetrators who commit these private/residential attacks tend to be psychologically and behaviorally different from public mass shooting offenders (Krouse & Richardson, 2015;Silva, 2022a).…”
mentioning
confidence: 99%